2004
DOI: 10.1002/ajmg.b.30034
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglyphic profile in 22q deletion syndrome

Abstract: A genetic subtype of schizophrenia has been described in 22q11 Deletion syndrome. Previous studies have described an excess of dermatoglyphic alterations in schizophrenia, such as low a-b ridge counts (ABRCs), a high frequency of ridge dissociations, and increased dermatoglyphic fluctuating asymmetry. Little is known however, about the dermatoglyphic profile of 22qDS subjects showing psychotic symptoms and its similarity to the previously reported anomalies in schizophrenia. We studied the palmar dermatoglyphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Also, it was reported that total finger ridge count was reduced in patients with schizophrenia [ 13 , 19 ]. Moreover, value of “atd” angle is observed in higher as compared in general population [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was reported that total finger ridge count was reduced in patients with schizophrenia [ 13 , 19 ]. Moreover, value of “atd” angle is observed in higher as compared in general population [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicating a link between chromosomal anomalies and alterations in dermatoglyphic and palmar flexion creases suggests genetic influences on the formation of DAs as well (Reed, 1981). Deviant ATD angles have been associated with chromosomal syndromes; namely, in 22q Deletion Syndrome patients, those with mental retardation had greater ATD angles than those with psychotic symptoms, who both had greater angles than healthy controls (Martín et al, 2004). More specifically pertaining to schizophrenia, a family study of people with a schizophrenia spectrum disorder and their first-degree relatives found associations between both genetically-influenced ectodermal derivate abnormalities (e.g., ridge dissociation, abnormal palmar flexion creases) and environmentally-influenced abnormalities such as total a-b ridge count and schizophrenia vulnerability (Fatjó-Vilas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, due to their polygenic determination, genes underlying certain disorder may, by pleiotropy, affect dermatoglyphic parameters [12]. This makes them, along with lifetime permanence and the fact that forces that channel ridge differentiation must be operating prior the 19 th week of gestation, a sensitive indicator of intrauterine disturbances associated with chromosomal/gene abnormalities, environmental stress, or a combination of these [28]. Altered dermatoglyphic configuration has been proven in numerous multifactorial or chromosomal disorders [22,28,35].…”
Section: Introductionmentioning
confidence: 99%